2015
DOI: 10.1890/15-1437
|View full text |Cite
|
Sign up to set email alerts
|

Does ecosystem sensitivity to precipitation at the site-level conform to regional-scale predictions?

Abstract: Abstract. Central to understanding global C cycle dynamics is the functional relationship between precipitation and net primary production (NPP). At large spatial (regional) scales, the responsiveness of aboveground NPP (ANPP) to interannual variation in annual precipitation (AP; ANPP sens ) is inversely related to site-level ANPP, coinciding with turnover of plant communities along precipitation gradients. Within ecosystems experiencing chronic alterations in water availability, plant community change will al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(63 citation statements)
references
References 12 publications
5
58
0
Order By: Relevance
“…The Konza Prairie (KNZ) is a Long‐Term Ecological Research site located in the Flint Hills of northeastern Kansas (Wilcox et al. ). KNZ is a native tallgrass prairie.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Konza Prairie (KNZ) is a Long‐Term Ecological Research site located in the Flint Hills of northeastern Kansas (Wilcox et al. ). KNZ is a native tallgrass prairie.…”
Section: Methodsmentioning
confidence: 99%
“…The details of the KNZ ANPP data are described in Wilcox et al. , . The data from the KNZ site came from the upland site representing typical ANPP observed at the KNZ site located on more shallow, rocky soils (Knapp et al.…”
Section: Methodsmentioning
confidence: 99%
“…Precipitation is a predominant climatic factor that controls plant growth and distribution across most of the globe, particularly in arid and semi‐arid grasslands (Knapp, Ciais, & Smith, ; Yang, Fang, Ma, & Wang, ). In the past few decades, numerous studies documenting above‐ground net primary production (ANPP) in response to precipitation changes have developed two distinct models: temporal models—ANPP increases linearly with increasing annual precipitation amount at one site, and spatial models—ANPP increases nonlinearly to saturation across arid to extremely humid sites (Huxman et al, ; Ponce‐Campos et al, ; Wilcox, Blair, Smith, & Knapp, ; Yahdjian & Sala, ). However, some studies have shown inconsistent results.…”
Section: Introductionmentioning
confidence: 99%
“…Climate warming has been demonstrated to influence community structure242526 and species interactions272829 that could potentially translate into changes in community biomass stability303132. Likewise, changes in precipitation could alter community biomass production33, species diversity34 and species relative abundance patterns35 that may also have consequences for biomass stability1617. Notably, the effects of climate warming and altered precipitation on community properties, including stability, may not be independent of each other, given that warming is expected to impose its strongest effect under drought conditions333637.…”
mentioning
confidence: 99%